Implementation of Restorative Justice Principles in Indonesia: A Review - Eva Achjani Zulfa (International Journal of Science and Society, 2020)
Restorative justice is a phrase that is very popular among law enforcers understood in various dimensions. Simple questions about restorative justice whether a "principle" or "value" or "mechanism or even" program "is interesting to look at the understanding of policymakers and law enforcers as executors in line with efforts to implement it within the criminal equity framework and preventive endeavors and wrongdoing anticipation based on the current legitimate framework that's broadly pertinent in nations around the world. This paper is a literature study that uses secondary data with a qualitative analysis that is used to describe the development of an understanding of restorative justice.